Studi Komposisi, Struktur Tegakan dan Pola Distribusi Pohon di Area Terbuka Hijau di Provinsi Jambi: The Study Composition,The Structure of Stand and The Pattern of Distribution Trees at Open Space Green Area in Jambi Province - Nursanti, Nursanti; Gani, Qori Anithya; Farikhah, Anisatul (Fakultas Kehutanan Universitas Jambi, 2026)
ABSTRACT Efforts that can be made by the government to overcome the problems of global warming, air pollution and air temperature, garbage and flooding as well as other ecological problems are through the development of Green Open Space (RTH). This study was conducted to determine the diversity of species and distribution patterns of dominant tree species in green open spaces in Jambi City, especially in the area of ​​the Jambi University Educational Forest and the Bagan Pete City Forest of Jambi City. This study was conducted for 3 (three) months from March to May 2016. Found 376 individuals of 52 species in the Jambi University Educational Forest, and 242 individuals of 49 tree species in the Bagan Pete City Forest of Jambi City The diversity index (H ') in the Jambi University Educational Forest is higher than in the Bagan Pete City Forest. The dominant species in the Jambi University Educational Forest are spread in groups for the types of Endospermum mallacense, Alstonia scholaris, Porterandia anisophylla, Macaranga gigantea, Garcinia parvifolia, Artocarpus odoratissimus, Antidesma cuspidatum, Litsea umbellata. Uniform distribution pattern for Gironniera nervosa and Rhodamnia cinerea species. Dominant tree species in Bagan Pete City Forest, Jambi City are uniformly distributed for Sloetia elongata, Gironniera subaequalis Macaranga constricta, Alstonia scholaris, Artocarpus elasticus, and Sizygium sp. Clustered distribution pattern for Porterandia anisophylla, Hevea brasiliensis, Endospermum mallacense, and Antidesma coriacea species. Keywords: ecological, green open space, species composition, vegetation analysis ABSTRAK Upaya yang dapat dilakukan oleh pemerintah untuk mengatasi permasalahan pemanasan global, polusi udara dan suhu udara, sampah dan banjir serta permasalahan ekologis lainnya yaitu melalui pengembangan Ruang Terbuka Hijau (RTH). Penelitian ini dilakukan untuk mengetahui keanekaragaman jenis dan pola penyebaran jenis-jenis pohon dominan di ruang terbuka hijau di Kota jambi, khususnya pada kawasan Hutan Pendidikan Universitas Jambi dan Hutan Kota Bagan Pete Kota Jambi. Penelitian ini dilaksanakan selama 3 (tiga) bulan pada Bulan Maret sampai dengan Mei 2016. Ditemukan 376 individu dari 52 spesies Pada Hutan Pendidikan Universitas Jambi, dan 242 individu dari 49 spesies pohon di Hutan Kota Bagan Pete Kota Jambi Indeks keanekaragaman (H’) pada Hutan Pendidikan Universitas Jambi lebih tinggi dibandingkan pada Hutan Kota Bagan Pete. Jenis dominan di Hutan Pendidikan Universitas Jambi menyebar mengelompok untuk jenis Endospermum mallacense, Alstonia scholaris, Porterandia anisophylla, Macaranga gigantea, Garcinia parvifolia, Artocarpus odoratissimus, Antidesma cuspidatum, Litsea umbellata. Pola sebaran seragam untuk jenis Gironniera nervosa dan Rhodamnia cinerea. Jenis pohon dominan pada Hutan Kota Bagan Pete Kota Jambi menyebar seragam untuk jenis Sloetia elongata, Gironniera subaequalis Macaranga constricta, Alstonia scholaris, Artocarpus elasticus, dan Sizygium sp. Pola sebaran mengelompok untuk jenis Porterandia anisophylla, Hevea brasiliensis, Endospermum mallacense, dan Antidesma coriacea. Kata kunci: analisis vegetasi, ekologi, komposisi jenis, ruang terbuka hijau